Engineering Optimization of a BFS Packaging Process for Pediatric Oral Rehydration Solutions: Impact on CAPEX, COGS, OEE, and Time to Market - Yuldashev, Bekhzad (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2023)
This study evaluates the engineering optimization of a Blow-Fill-Seal (BFS) production line at the Samarkand England Eco-Medical (SEEM) plant. Amidst the transformation of Uzbekistan’s pharmaceutical industry, the project focused on localizing the pediatric oral rehydration product REGIDREYD and expanding the line to include REGIDREYD ZINC. By reconfiguring a BFS line originally designed for intravenous (IV) fluids specifically removing the rubber cap assembly for a dedicated oral format the study assesses the impact on Overall Equipment Effectiveness (OEE), Capital Expenditure (CAPEX), and Cost of Goods Sold (COGS). Results indicate that reengineering existing assets achieved an OEE of over 81% and secured official state registration (DV/M 03775/03/21), while also enabling contract manufacturing for external brands such as REGIDOL.